The direct and indirect effects of COVID‐19 pandemic in a real‐life hematological setting. Issue 4 (3rd March 2021) - Condom, Maria; Mussetti, Alberto; Maluquer, Clara; Parody, Rocío; González‐Barca, Eva; Arnan, Montserrat; Albasanz‐Puig, Adaia; Pomares, Helena; Salas, Maria Queralt; Carro, Itziar; Peña, Marta; Clapes, Victòria; et al.
Abstract: Background: Clinical outcomes of novel coronavirus 2019 disease (COVID‐19) in onco‐hematological patients are unknown. When compared to non‐immunocompromised patients, onco‐hematological patients seem to have higher mortality rates. Aims: We describe the characteristics and outcomes of a consecutive cohort of 24 onco‐hematological patients with COVID‐19 during the first month of the pandemic. We also describe variations in healthcare resource utilization within our hematology department. Methods and Results: Data from patients between the first month of the pandemic were retrospectively collected. Clinical and logistic data were also collected and compared with the average values from the prior 3 months of activity. Prevalence of COVID‐19 in our hematological population was 0.4%. Baseline characteristics were as follows: male sex: 83%, lymphoid diseases: 46%, median age: 69 (22‐82) years. Median follow‐up in survivors was 14 (9‐28) days and inpatient mortality rate was 46%. Average time to moderate/severe respiratory insufficiency and death were 3 (1‐10) and 10 (3‐18) days, respectively. Only 1 out of every 12 patients who developed moderate to severe respiratory insufficiency recovered. Upon univariate analysis, the following factors were associated with higher mortality: age ≥ 70 years ( P  = .01) and D‐dimer ≥900 mcg/L ( P  = .04). With respect to indirect effects during the COVID‐19 pandemic, and when compared with the prior 3 months of activity, inpatient mortality (excluding patients with COVID‐19 included in the study) increased by 56%. This was associated with a more frequent use of vasoactive drugs (+300%) and advanced respiratory support (+133%) in the hematology ward. In the outpatient setting, there was a reduction in initial visits (−55%) and chemotherapy sessions (−19%). A significant increase in phone visits was reported (+581%). Conclusion: COVID‐19 pandemic is associated with elevated mortality in hematological patients. Negative indirect effects are also evident within this setting.